Strategi Coping Stress Guru Non-Pendidikan Khusus dalam Mengajar Anak Berkebutuhan Khusus: Studi Fenomenologi di Sekolah Reguler Surabaya - Azkia Putri Yasmin; Ira Darmawanti (SENTRI: Jurnal Riset Ilmiah, 2026)
This study focused on stress coping strategies used by non-special education teachers in teaching children with special needs in regular schools. This study used a qualitative method with an interpretative phenomenology technique to collect data through semistructured interviews with non-special education teachers who have experience teaching children with disabilities. The results of this study show that teachers experience various forms of emotional and pedagogical stress, especially related to children’s aggressions and tantrum behavior, communication limitations and lack of cooperation with parents of children with disabilities. In dealing with these conditions, teacher apply a combination of emotion-focused coping and problem-focused coping strategies, such an emotion management, self acceptance, adjusting learning strategies, individualized approaches and others. However, the application of coping strategies faces issues such as challenge in collaboration with parents and limited teacher knowledge.